2011
DOI: 10.4317/medoral.17260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-therapeutic management of drooling: Review and update

Abstract: Drooling is the uncontrolled leakage of saliva outside the mouth, generally as a result of difficulty in swallowing the saliva produced. Many factors contribute to drooling, though it is more commonly seen in children with brain paralysis -particularly those receiving anticonvulsivant medication. Drooling is also often seen in patients with lip sealing problems or malocclusions such as anterior open bite. Clinically, the affected patients can develop skin irritation or abrasions, problems of hygiene, unpleasan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…As drooling is a multifactorial problem, it requires careful assessment by the multidisciplinary team, focusing on medical history and possible aetiology 1,5,7,13. The neurological examination should focus on the facial and hypoglossal nerves, posture, tone and motor skills 5…”
Section: Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As drooling is a multifactorial problem, it requires careful assessment by the multidisciplinary team, focusing on medical history and possible aetiology 1,5,7,13. The neurological examination should focus on the facial and hypoglossal nerves, posture, tone and motor skills 5…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…with Candida albicans ) 7,9,10. Drooling can also impact on speech and eating skills, and cause dehydration 5,10,11. Associated physical, psychological and practical factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, loss of motor neurons in the spinal cord causes muscular weakness and atrophy, leading in turn to progressive respiratory dysfunction, labored communication, and decreased voluntary as well as reflexive coughing. [5][6][7][8] In ALS, sialorrhea is caused mostly by a decreased ability to swallow secretions (not by increased saliva production) due to tongue spasticity, orofacial and palatinolingual muscle control failure, facial weakness, and inability to maintain oral and buccal competence. 9,10 The progressive weakness of facial muscles and difficulty in swallowing saliva leads to drooling.…”
Section: Introductionmentioning
confidence: 99%
“…8,[18][19][20][21] Drooling also causes dermatologic problems, such as facial irritation and skin excoriation. 5 Although pulmonary aspiration syndromes are often misdiagnosed in patients with ALS, they are associated with a high mortality. 8 In a cohort of 40 consecutive patients with ALS, Sorenson et al 18 observed the occurrence of aspiration pneumonia in 5 cases (13%).…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, é possível que o paciente melhore alguns componentes da deglutição de forma consciente. A técnica pode ter um impacto positivo no treinamento do paciente e na melhoria da função oromotora 14 . Ao indicar um tratamento para o controle da sialorreia em crianças com PC, é necessário considerar a oportunidade de acesso dos pacientes ao método proposto, tendo em vista as condições financeiras, sociais e culturais de cada família.…”
unclassified